1975
DOI: 10.1113/jphysiol.1975.sp010865
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of calcium in pancreatic juice.

Abstract: SUMMARY1. The origin of the calcium secreted by the pancreas has been investigated in vivo in the guinea-pig by a study carried out in parallel (a) in the juice secreted in response to the injection of either secretin or caerulein and (b) in the pancreatic tissue and in cell fractions isolated therefrom.2. In agreement with previous findings we observed that the concentration of calcium is low in the secretin-stimulated and high in the caeruleinstimulated juice. In the latter calcium and protein are proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
1

Year Published

1975
1975
1989
1989

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 32 publications
(42 reference statements)
4
20
1
Order By: Relevance
“…These findings further confirm the idea that in the pancreas, as previously suggested in other secretory systems (Berneis et al, 1969;Wallach & Schramm, 1971), the role of the calcium segregated within the secretion granules might be concerned not with the regulation of the cellular activity but with the architecture of the granules themselves and with the functionality of the released secretion products Ceccarelli, Clemente & Meldolesi, 1975).…”
Section: Discussionsupporting
confidence: 79%
“…These findings further confirm the idea that in the pancreas, as previously suggested in other secretory systems (Berneis et al, 1969;Wallach & Schramm, 1971), the role of the calcium segregated within the secretion granules might be concerned not with the regulation of the cellular activity but with the architecture of the granules themselves and with the functionality of the released secretion products Ceccarelli, Clemente & Meldolesi, 1975).…”
Section: Discussionsupporting
confidence: 79%
“…Other studies on the exocrine pancreas and parotid gland have also noted similarities in the composition of the secretary granules and gland secretion (Wallach'& Schramm, 1971;Ceccarelli, Clemente & Meldolesi, 1975 Wallach & Schramm (1971) have however, shown that only 14 % of the granule Ca2+ is tightly associated with proteins. There is also considerable evidence to suggest that the effects ofadrenergic and cholinergic stimulation on the movement ofexchangeable Ca2+ across the plasma membrane is independent of amylase secretion (Kanagasuntheram & Randle, 1976;Miller & Nelson, 1977;Kusek, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…The rest comes from different sources which might be either the interstitial fluid or a different pathway operating in the acinar cells, or both (56). The existence of multiple sources of calcium in the pancreatic secretion could be one of the numerous mechanisms which contribute to switch the conditions for the activation of the proteolytic zymogens from unfavorable, as in ZG, to favorable, as in the intestinal lumen.…”
Section: Discussionmentioning
confidence: 99%